Socially Responsible Investment in Human Capital - Tutova, О. (Економіко-математичне моделювання соціально-економічних систем, 2017)
An overview of contemporary economical concepts of sustainable capital, human-resource capitalism, sustainable development, sustainable society, and socially responsible investment is made. The main features of a sustainable society are examined. The problem of measurement of the impact of social investment in human development is analyzed.